2022
DOI: 10.1155/2022/7950834
|View full text |Cite
|
Sign up to set email alerts
|

Immunological Risk Assessment of Xenogeneic Dural Patch by Comparing with Raw Material via GTKO Mice

Abstract: Objective. In this study, α-Gal epitope-deficient (GGTA1 knockout (GTKO)) mice were used to assess the immunological risks of xenogeneic dural patch by comparing with raw material. Methods. The xenogeneic dural patch (T2) was prepared from bovine pericardium (T1, raw material) through decellularization and carboxymethyl chitosan (CMCS) coating. Transmission electron microscopy (TEM) and scanning electron microscopy (SEM) were used to characterize the collagen fibers and surface microstructural changes in the T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Semi-quantitative histological evaluation in experimental animals for local tissue responses, in comparison with that of reference material, is the gold standard for assessing the potential safety of any biomaterial. 47 Pure 3D-printed PLA scaffolds serve as the reference material for the evaluation. 34 The semi-quantitative parameters evaluated were summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Semi-quantitative histological evaluation in experimental animals for local tissue responses, in comparison with that of reference material, is the gold standard for assessing the potential safety of any biomaterial. 47 Pure 3D-printed PLA scaffolds serve as the reference material for the evaluation. 34 The semi-quantitative parameters evaluated were summarized in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Owing to the development of gene-editing technology, GTKO mice have been established and used to study the specific mechanism of xenograft rejection [ 11 , 12 ]. We have successfully established a GTKO mouse model using gene targeting techniques (homologous arm recombination) [ 10 , [12] , [13] , [14] ] and revealed that anti-Gal antibody levels increased significantly after implantation of xenogeneic bone matrix or xenogeneic decellularized cornea in GTKO mice. However, due to the small size of GTKO mice, it is difficult to assess the biocompatibility and effectiveness of xenografts via in situ implantation.…”
Section: Introductionmentioning
confidence: 99%